Harmonization of Examination Methodologies: A Crucial Institutional Component of Forensic Science in the Russian Federation - Marina V. Zhizhina (Теория и практика судебной экспертизы)
A unified methodological approach is critical to obtaining objective and scientifically sound results in forensic practice. Such an approach ensures that different practitioners working with the same physical evidence will obtain comparable results. This, in turn, guarantees that the most important principles of forensic science are upheld, namely, that examinations are conducted objectively, comprehensively and exhaustively, with the possibility of further verification of reliability and validity of the expert’s conclusions.In this regard, standardization and harmonization of scientific methodologies supporting forensic operations are the cornerstone of the reform of the modern institution of forensic science in the Russian Federation, as well as an integral part of the judicial reform. The current state of methodological support in the system of state and non-state forensic science organizations in Russia is analyzed. The author presents the case for mandatory certification of forensic methods and proposes a range of measures to advance the harmonization of forensic methodologies in forensic practice.